A study of quality tools and techniques employed in Perlis and Kedah manufacturing companies - Che Padzilah, Yaacob
Quality tools and technique can be used to achieve continuous improvement of quality in the manufacturing industry. This research is focused on manufacturing companies located in the states of Perlis and Kedah. The study examines whether manufacturing companies employ quality tools and techniques in their daily operations. In addition, it identifies the problems and challenges faced during the implementation of the tools and techniques on the manufacturing shop floor. The study uses mail questionnaires and structured interviews as its main instruments of data collection. In this study four hypotheses are developed based on the theoretical framework, of which the variables are in the categories of independent, dependent and moderating variables. Independent variables comprise of company location, number of years the company has been operating (referred to as “level of maturity”), annual sales turnover, number of full time employees, product(s) of the company, and quality standard certification. Meanwhile, the dependent variables are the issues in the implementation of quality tools and techniques, and how quality tools and techniques help the companies. Moderating variables in this research are the actual use of quality tools and techniques and information regarding the respondents who answered the questionnaire on behalf of the company. Data was analysed using independent T-Test and one-way analysis of variance (ANOVA) and the results helped to identify the problems and challenges faced during the implementation of the tools and techniques. The findings of this study reveal that quality tools and techniques are indeed being used by the companies but each with varying degree. The results reveal that companies that implement ISO 9000 quality system tend to use more quality tools and techniques compared to companies without quality systems. The study indicated that high sales turnover has no impact on planning, budget and training as well as the implementation of quality tools and techniques. It also indicates that the level of maturity does not have any bearing on the implementation of quality tools and techniques. Lastly, higher numbers of work forces do not necessarily bring about issues of communication and teamwork in order to implement quality tools and techniques in the company. In conclusion, the overall results from this study show that training, teamwork, communication, planning, and budgeting have no impact at the companies in Perlis and Kedah.